A Survey on Collaboration Rate of Authors in the Journal of Linguistic and Rhotorical Studies - Rahman Marefat; abdolazim veloie; Marzieh Azodi (مطالعات زبانی و بلاغی)
The main aim of this article is investigating the collaboration rate of authors of the journal of Linguistic and Rhetorical Studies via using scientometrics methods. The total issues of the JLRS which have been published during 2010-2018 was the subject of this research. The results showed that 215 authors had published 118 articles in JLRS and mean number of authors per article is1.8. From the viewpoint of gender, 64.6% of authors are men and 35.4% are women. The results also showed that the Semnan University is most prolific among other research institutes and scientific centers. Results also indicated that other universities such as Bu-Ali Sina University, University of Mazandaran, Allameh Tabataba'i University were in next situation. The results highlighted that collaboration coefficient was 0/4.